2021
DOI: 10.1177/87552930211057581
|View full text |Cite
|
Sign up to set email alerts
|

Self-centering seismic-resistant structures: Historical overview and state-of-the-art

Abstract: This state-of-the-art review provides an overview of the evolution of self-centering structures from early historical structures that inherently exhibited a recentering response to modern systems engineered for enhanced seismic resilience. From the early research investigations that were conducted since the 1960s, to the sharp increase of interest in this topic over the last two decades, self-centering seismic-resistant structures that can mitigate both damage and residual drifts following major earthquakes ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 199 publications
(244 reference statements)
0
26
0
Order By: Relevance
“…Connections between the rocking core wall and the gravity system elements also require special consideration to accommodate the rocking-induced uplift of the core wall relative to the gravity systems while properly transferring the inertial forces from the gravity systems to the core wall. Different types of connections have been proposed for typical rocking frame and wall systems [40][41][42] that can be used in the SCRIP system as well to decouple the core wall uplift from the gravity system.…”
Section: Design Of the Moment Base-mechanismmentioning
confidence: 99%
“…Connections between the rocking core wall and the gravity system elements also require special consideration to accommodate the rocking-induced uplift of the core wall relative to the gravity systems while properly transferring the inertial forces from the gravity systems to the core wall. Different types of connections have been proposed for typical rocking frame and wall systems [40][41][42] that can be used in the SCRIP system as well to decouple the core wall uplift from the gravity system.…”
Section: Design Of the Moment Base-mechanismmentioning
confidence: 99%
“…It is worth studying because it can describe a plethora of structures: First, since uplift works as a mechanical fuse, rocking can be used as a seismic design strategy for both bridges and buildings. 23,[25][26][27][28][29][30][31][32][33] Second, the out-of-plane response of masonry walls is a form of rocking motion. [34][35][36][37][38][39][40][41][42][43][44][45][46][47] Third, ancient Greco-Roman and Chinese temples, as well as other monumental structures of historical significance respond mainly in rocking mode.…”
Section: Introductionmentioning
confidence: 99%
“…82 Notably, the concept of statistical validation could also be applied to Masonry and Reinforced Concrete structures. 83,84 Reggiani Manzo et al showed 23 that the response of a rocking structure made of precast RC elements was also predictable in the statistical sense.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations